Uric acid and blood pressures in low birth weight 7-year-olds - Paulus Linardi; Adrian Umboh; Suryadi NN Tatura (Indonesian Pediatric Society, 2014)
Background Low birth weight (LBW) has been associated withincreased cardiovascular diseases, including hypertension, duringadulthood. Nephrogenesis impairment in LBW may lead to anincrease of uric acid and hypertension.Objective To assess for a correlation between uric acid and bloodpressures in LBW children.Methods This study was conducted from January to April 20 12.A comparative and correlative analytic-observational study with across-sectional method was done in children aged 7-8 years, bornat Prof. Dr. RD Kandou General Hospital and living in Manado.Forty-eight LBW children and 48 normal birth weight (NBW)children were included in this study. All children underwent uricacid level and blood pressures measurements.Results Mean uric acid level in LBW children was significantlyhigher than in NBW children (P = 0.001) . There was no correlationbetween uric acid and blood pressures in LBW children(r=0.13,P> 0.05 for systolic blood pressure; r=0.05, P> 0.05 for diastolicblood pressure).Conclusioru; LBW children have higher uric acid levels thanNBW children, but no correlation is found between uric acid leveland blood pressures.